In Vitro Blood–Brain Barrier Models—An Overview of Established Models and New Microfluidic Approaches. Issue 9 (28th January 2015) - Wolff, Anette; Antfolk, Maria; Brodin, Birger; Tenje, Maria; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; Tamai, Ikumi; Vig, Balvinder; Yu, Lawrence X.
<x xml:space="preserve">Abstract</x> The societal need for new central nervous system (CNS) medicines is substantial, because of the global increase in life expectancy and the accompanying increase in age‐related CNS diseases. Low blood–brain barrier (BBB) permeability has been one of the major causes of failure for new CNS drug candidates. There has therefore been a great interest in cell models, which mimic BBB permeation properties. In this review, we present an overview of the performance of monocultured, cocultured, and triple‐cultured primary cells and immortalized cell lines, including key parameters such as transendothelial electrical resistance values, permeabilities of paracellular flux markers, and expression of BBB‐specific marker proteins. Microfluidic systems are gaining ground as a new automated technical platform for cell culture and systematic analysis. The performance of these systems was compared with current state‐of‐the‐art models and it was noted that, although they show great promise, these systems have not yet reached beyond the proof‐of‐concept stage. In general, it was found that there were large variations in experimental protocols, BBB phenotype markers, and paracellular flux markers used. It is the author's opinion that the field may benefit greatly from developing standardized methodologies and initiating collaborative efforts on optimizing culture protocols. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:2727–2746, 2015